Spotted fever rickettsiosis in a wildlife researcher in Sabah, Malaysia: A case study - Salgado Lynn, M; William, T; Tanganuchitcharnchai, A; Jintaworn, S; Thaipadungpanit, J; Lee, M; Jalius, C; Daszak, P; Goossens, B; Hughes, T; Blacksell, S (MDPI, 2018)
We present evidence for a case of spotted fever rickettsiosis with severe complications in a young adult male. Although spotted fever group rickettsiae (SFGR) have been reported as the most prevalent cause of rickettsiosis in rural areas of Sabah, Malaysia since the 1980s, this is the first detailed case report of suspected SFGR in the state. Current data on the prevalence, type, and thorough clinical reports on complications of SFGR and other rickettsioses in Sabah is lacking and required to raise the awareness of such diseases. There is a need to emphasize the screening of rickettsioses to medical personnel and to encourage the use of appropriate antibiotics as early treatment for nonspecific febrile illnesses in this region. Suspected rickettsioses need to be considered as one of the differential diagnoses for patients presenting with acute febrile illness for laboratory investigations, and early treatment instituted.